Acute heat-stress effects on physiology and fear-related behaviour in red jungle fowl and domestic fowl - Zulkifli, I.; Dass, R. T.; Che Norma, M. T. (Canadian Science Publishing, 1999)
Two experiments were conducted to compare heat tolerance of red jungle fowl (RJF) and commercial broilers (CB) at (i) a common age and (ii) a common body weight. In exp. 1, RJF and CB of a common age (8 wk) were exposed to 36 ± 1°C for 6 h. RJF had smaller increases in heterophil to lymphocyte ratios and body temperature and higher serum cholesterol concentrations than CB in response to the heat treatment, while tonic immobility (TI) measurements were not affected by heat stress. In exp. 2, RJF and CB of a common body weight (1000 ± 150 g) were subjected to similar procedures as in exp. 1 (except TI durations). Both breeds responded similarly to the heat treatment. In both experiments, RJF had higher serum glucose level than CB, and the trait was not affected by heat exposure. Key words: Heat stress, physiology, fear, jungle fowl, broilers